2003
DOI: 10.1002/jsfa.1376
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stabilization of cold‐pressed sunflower oil using phenolic compounds of the same seeds

Abstract: It is known that sunflower seeds are rich in phenols, constituting approximately 1-3 g per 100 g of seeds. The principal phenol is chlorogenic acid (CGA), followed by caffeic acid (CA) and lower quantities of several other compounds. On the contrary, it is known that phenols are present only in trace amounts in cold-pressed sunflower seed oils. In this study, the possibility of improving the oxidative stability of cold-pressed sunflower oil is evaluated using phenolic substances constitutive of seeds. Phenols,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 22 publications
2
38
0
6
Order By: Relevance
“…Seed oils are generally poor of phenol compounds [6,7]. It was confirmed by our analytical results, whereonly 5.7 mg/L of phenols expressed as gallic acid were found in MIX C. With enrichment of oil in biophenols deriving from OMWW, a value of 339.8 mg/L of gallic acid was reached in fresh MIX P, an amount of about sixty times greater than the control.…”
Section: Biophenolssupporting
confidence: 81%
See 1 more Smart Citation
“…Seed oils are generally poor of phenol compounds [6,7]. It was confirmed by our analytical results, whereonly 5.7 mg/L of phenols expressed as gallic acid were found in MIX C. With enrichment of oil in biophenols deriving from OMWW, a value of 339.8 mg/L of gallic acid was reached in fresh MIX P, an amount of about sixty times greater than the control.…”
Section: Biophenolssupporting
confidence: 81%
“…Seed oils are generally poorer of phenolic compounds than olive oils [6,7]. The aim of this study was to evaluate oxidation stability of high oleic oil enriched in biophenols, comparing its performance with that of the same oil where no phenols were added, during discontinuous and prolonged thermal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of the Rancimat test, the IP values (at 110°C) of the investigated oil samples (Table 4) were in the range from 3.63 h to 4.63 h, which is somewhat higher compared to the findings of De Leonardis et al (2003), who reported a value of 2.63 hours.…”
Section: Resultsmentioning
confidence: 53%
“…This assumes oil preparation solely by mechanical pressing on a screw press. After pressing, the oil is additionally purified by filtration or sedimentation, while no further quality improvement by refining is allowed (De Leonardis et al 2003;Matthäus & Spener 2008). Recent technological developments have enabled the manufacture of high-quality unrefined oils to be economically justified (Lanzani et al 1988;Contini & Moresi 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation